Dual radio communication device and method of operation thereof - WU WEIDE; LIAO YIRU (2024)
Embodiments of the present application provide a dual radio communication device and an operating method thereof, including an operating method performed by a wireless communication device, the method comprising: in response to a wireless signal being a first type signal on a high performance radio layer, determining a first type signal on the high performance radio layer; selecting a high performance receiver to receive the wireless signal from a transmission device; and in response to the wireless signal being a second type signal on a low power radio layer, selecting a low power receiver or the high performance receiver to receive the wireless signal from the transmitting device. 本申请实施例提供一种双无线电通信装置及其操作方法，包括一种操作方法，由一无线通信装置执行，所述方法包括：响应于一无线信号是在一高性能无线电层上的一第一类型信号，选择一高性能接收器来接收来自一传送装置的所述无线信号；以及响应于所述无线信号是在一低功率无线电层上的一第二类型信号，选择一低功率接收器或所述高性能接收器来接收从所述传送装置的所述无线信号。